Existence and Dynamics of Hajj and Umrah Guidance Groups in Bogor and Jember Regency - Abidin, Zaenal; Dwijayanto, Arik; Dali, Azharuddin Mohd (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The community highly trusts Islamic boarding schools as religious, educational institutions in religious formation. Many Islamic boarding schools are participating in the Hajj and Umrah guidance business by establishing the Hajj and Umrah Guidance Group (KBIHU). This article aims to analyze the dynamics of Islamic boarding school-based KBIHU in guiding the Hajj and Umrah in Bogor Regency and Jember Regency. This article uses an ethnographic approach with data collection techniques through interviews and observations conducted at KBIHU in Bogor and Jember. The results of this study show that the presence of KBIHU helps the government's duties and functions in carrying out guidance to Hajj pilgrims as regulated in the Decree of the Director General of Hajj and Umrah Organization (Dirjen PHU) Number 59 of 2019 concerning Operational Guidelines for Guidance Groups. The existence of Islamic boarding school-based KBIHU generally depends on the quality of human resources in management and supervisors. Kiai, as Islamic boarding school caregivers, have qualified knowledge but still need to be competent in guidance and have certificates. They must be more competent in secretarial procedures, guidance agreement documents, participant data, and guidance plans. The supervisory agencies for KBIHU, such as the Directorate General of PHU, the PHU Division of the Regional Office, and the PHU Section of the Ministry of Religion, have not fully implemented the Decree of the Director General of PHU 59 of 2019 in terms of guidance, supervision, control and reporting by the provisions of this decision. In carrying out accreditation, the Regional Office of the Ministry of Religion must involve professional institutions to guide KBIHU in reporting, documents and all its obligations. KBIHU reporting and documents must be done digitally using the PUSAKA Application as the Ministry of Religion's Super Apps. Increasing the capacity of KBIHU based on Islamic boarding schools can contribute to the development of foundations/Islamic boarding schools and provide knowledge to the community.